Proximate Composition, Qualitative Phytochemical Screening and In-Vitro Antioxidant Potential of Triumfetta rhomboidea Leaves Extracts - Akintimehin, Emmanuel; Onoagbe, Iyere; Abu, Osahon (Trends in Sciences, 2022)
Continuous exploration of medicinal plants for bioactive constituents is essential since the availability and activities of these compounds speaks volume of their possible medicinal benefits. This study evaluated the proximate composition, phytochemical constituents and antioxidant potential of Triumfetta rhomboidea leaf extract. Extraction of aqueous (AETR) and ethanol (EETR) extract were performed by maceration. Proximate composition of pulverized leaf sample was performed following Association of Official Analytical Chemists (AOAC) standards. Antioxidant capacity of extracts were evaluated by determining the total phenolics content (TPC), total flavonoid content (TFC), total antioxidant capacity (TAC), ferric reducing antioxidant power (FRAP) scavenging ability, reducing power (RP) and lipid peroxidation inhibition. Results of proximate analysis revealed 11.01 % moisture content, 3.38 % ash content, 15.15 % crude fiber, 7.34 % crude fat, 61.09 % carbohydrate content, 17.18 % protein content and 379.14 kJ energy value. The total phenol content in aqueous and ethanol extracts were 20.36 ± 0.27 and 12.66 ± 0.28 mg GAE/g, respectively. Total flavonoid was 18.18 ± 1.02 mg QE/g for aqueous and 22.27 ± 0.26 mg QE/g for ethanol extracts with antioxidant capacity of 16.34 ± 4.92 mg AAE/100 g and 48.16 ± 8.50 mg AAE/100 g, respectively. AETR demonstrated highest Fe (II) reducing ability with IC50 of 0.33 ± 0.04 and 0.36 ± 0.04 mg/mL for FRAP and RP activities. This study has demonstrated that T. rhomboidea leave possess biologically active constituents and could presumably perform free radical scavenging activities in reactive oxygen species related diseases. HIGHLIGHTS Triumfetta rhomboidea leaves demonstrated remarkable proximate composition and high energy value The aqueous extract demonstrated high saponin content compared to ethanol extract Aqueous solution (distilled water) has better extraction efficiency of phenolic compounds in leaves of Triumfetta rhomboidea compared to ethanol The aqueous extract exhibited high antioxidant potential compared to ethanol extract as revealed by the ferric reducing antioxidant power and reducing power GRAPHICAL ABSTRACT